The effect of financial literacy, financial self-efficacy and locus of control on the financial behaviour of Bengkulu University students - Markus Leo Boangmanalu; Sri Adji Prabawa (Jurnal Mantik, 2024)
The ability to manage finances and decide on business strategies needs to be supported by a locus of control, mastery of adequate financial literacy skills, and confidence in one's ability to produce good finances (financial self-efficacy) in managing finances. This is a quantitative study aimed at determining the effect of independent variables (financial literacy, financial self-efficacy, and locus of control) on the dependent variable (financial behaviour) in Bengkulu University students. The implementation of this research uses a questionnaire method with the data analysed referring to the Likert scale. Active students of Bengkulu University class of 2020 were used as the population of this study and utilised purposive sampling method as the sampling technique. The sample used was 150 Bengkulu University students. The results of this study are that there is a positive and significant influence between financial literacy on the financial behavior of Bengkulu university students, there is a significant and positive influence between financial self-efficacy on the financial behavior of Bengkulu University students, and there is a significant and positive influence between locus of control on the financial behavior of Bengkulu University students.